West Papua Regional Police Efforts in Handling Illegal Mining Crimes in Manokwari Regency - Sroyer, Dance Markus; Balubun, Daud Daniel; Hammar, Imanuel I.R. (LEGAL BRIEF, 2025)
This study examines the efforts of the West Papua Regional Police in addressing illegal mining crimes in Manokwari Regency, a region rich in mineral resources yet vulnerable to environmental degradation and social conflict. Illegal mining persists due to economic pressures, weak governance, difficult geographical access, and limited enforcement capacity. Using a normative juridical approach supported by statutory, conceptual, and case analyses, this research identifies that illegal mining has caused severe ecological damage particularly river pollution and forest destruction—while generating social tensions related to indigenous land rights and depriving the local government of potential revenue. The West Papua Regional Police implement both penal and non-penal strategies grounded in the Mineral and Coal Mining Law and the National Police Law. Penal measures include investigation, prosecution, confiscation of mining equipment, and disruption of illegal logistics chains. Non-penal efforts involve preventive education, community outreach, and coordination with local stakeholders. However, enforcement remains constrained by socio-economic dependence on mining and resistance from customary communities. The study concludes that sustainable mitigation requires integrated law enforcement combined with government-supported economic empowerment programs to reduce community reliance on illegal mining.